Recent developments in the theory of diving - Eaves, G. (First International Symposium on "Biomechanics and Swimming, Waterpolo and Diving", 14-16 September 1970. Proceedings, 1971)
The failure of action-reaction theories to account for the rapid and apparently effortless spinning of the diver performing multiple twists has 1 ed to the appearance of what may be ea 11ed 11 di stortion" theories of twist. The basis of these is usually the concept of converting some of the somersault angular momentum into twist angular momentum and this concept has been shown to be invalid.